Determinants of Micro and Small Business Actors on the Motivation to Register for Free Halal Certification in Bondowoso Regency - Mahendra, Hairunnas Esa; Munir, Misbahul; Ridlwan, Mahmudah (Jurnal Internasional Ekonomi Islam, 2024)
Introduction: Government regulations on halal products, especially in the 2021 Job Creation Law, have been stipulated in the Halal Product Guarantee Law, this is an important factor for producers in the business sector related to halal products, especially since there is a free halal certification program. Objectives: The purpose of this study is to measure the motivation of micro and small business actors in Bondowoso Regency towards registering for free halal certification. Method: This study uses a quantitative approach with multiple linear regression analysis which aims to test the correlation of the variables of Government Regulation (X1), Halal Lifestyle (X2), Perceived Benefits of Halal Certification (X3), Business Competitiveness (X4), Product Safety and Hygiene (X5), to Motivation for Free Halal Certification Registration (Y1). Results: The results showed that government regulations, halal lifestyle, and product safety and hygiene had no significant partial effect on the motivation to register for free halal certification. Meanwhile, the perceived benefits of halal certification and business competitiveness have a partially significant effect on the motivation to register for free halal certification. However, these 5 variables simultaneously affect the motivation to register for free halal certification so it is worthy of being a construct of this study. Implications: The research will provide an overview of the relevant approaches that must be taken to attract micro and small business actors to register for free halal certification.